Case Report: Metaplastic breast carcinoma with osseous and chondrodifferentiation in liver metastasis: a rare case and review of literature - Li, Wenfang; Ou, Qin; Zhang, Tian-xiang; Long, Bin Bin; Zhou, Ke; Zhao, Lun Hua (Frontiers in Oncology, 2025)
BackgroundMetaplastic carcinoma of the breast with mesenchymal differentiation (MCMD) is a type of metaplastic breast carcinoma (MpBC) that is very rare and aggressive. The present case provides valuable information for clinicians on this MpBC.Case presentationA 41-year-old woman visited our hospital for a palpable painless mass in the left breast. Core needle biopsy (CNB) was performed, and the pathological result was infiltrating ductal carcinoma. Epirubicin (100 mg/m2) + cyclophosphamide (600 mg/m2) for four cycles was given. Color Doppler ultrasound examination indicated no obvious change in the size of the left breast mass. We changed to paclitaxel (175 mg/m2) for two cycles. Re-examination on April 26, 2018 with color Doppler ultrasound indicated that the tumor diameter increased to 8.39 cm × 8.07 cm × 6.19 cm. Radical resection of the left breast carcinoma was performed on June 04, 2018. The postoperative pathological results showed that the left breast tumor was composed of carcinoma and sarcoma components, without nerves and vascular invasion. The immunohistochemistry results were as follows: ER: (−), PR: (−), HER2: (−), CK5/6 (+), CK7: (+), E-cadherin (+), Ki67: 40% (+), P120: (+), P53 diffuse +, P63: (+), and S100 partially positive, GATA-3: (+). Four cycles of vinorelbine (25 mg/m2) + cisplatin (40 mg/m2) were performed after the operation. Enhanced CT indicated a 6.0 cm × 4.6 cm mass in the liver on January 1, 2019 through regular review, and liver lobectomy confirmed that metastasis originated from sarcoma components, together with bone and cartilage differentiation. The immunohistochemistry results indicated the following: ER (−), PR (−), GATA-3 (−), CD34 (+), P63 (−), CK8 (−), P40: (−), and vimentin: (+). The patient received oral anlotinib 12 mg once a day, with 2 weeks on/1 week off for eight cycles. The patient survived and showed no signs of recurrence at the follow-up visit.ConclusionThis case indicated that CNB may not always give an accurate diagnosis for MCMD. Neoadjuvant chemotherapy with epirubicin, cyclophosphamide, or paclitaxel for MCMD may not be effective for patients showing no sensitivity to these drugs. In addition, regular postoperative follow-up plays an important role in the early detection of remote metastasis, and timely surgical excision of a single metastatic lesion in the liver can lead to long-term progression-free survival (PFS).